STRENGTHENING OF THE CAST MACROGETHEROGENEOUS COMPOSITES - V. Ja. Kezik; A. S. Kalinchenko (Литьë и металлургия)
The influence of small additions into the liquid matrix alloys on the change in the solidification behavior of macroheterogeneous composite materials have been considered. It has been shown that additions of micro- and nano-size particles considerably improved mechanical properties of compozite materials.